ANALISIS MISKONSEPSI PESERTA DIDIK MENGGUNAKAN TES DIAGNOSTIK PADA MATERI USAHA DAN ENERGI DI SMA SUNGAI KEHIDUPAN - Pinoh, Petrus; Sitompul, Stepanus Sahala; Habellia, Ray Cinthya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Physics is a branch of science that investigates natural laws that are relevant to everyday life. The purpose of this research is to describe and to find out the causes of misconception in work and energy at students of SMA Sungai Kehidupan. The method of this research was qualitative descriptive method with a saturated sampling. The subject of the research was the entire population of class XA, XB and XI IPA which are 58 students. The data collection used was a diagnostic test with a multiple choice with closed reasons and interviews. The result of misconception in work and energy at students of SMA Sungai Kehidupan class XA, XB and XI IPA were a percentage of 75.86% regarding to work and energy. The profile of students"™ misconceptions found were five concepts, which are: understanding the definition of work and energy (57.47%); understanding "usaha pada bidang miring dan lingkaran (79.31%); identifying the relationship between work and kinetic energy (72.99%); identifying the kinetic energy of a moving object (71.84%); identifying the law of conservation of mechanical energy (78.16%). The cause of misconception of students are incomplete/wrong reasoning 60%; Students"™ learning interest 20%; Students"™ preconceptions 20%. These resuls are expected to be used as a material for consideration in choosing the appropriate treatment to overcome misconception of students.